Survival, Growth, and Productivity of Rhizophora racemosa Transplanted in Natural Ecosystems: Implications for Mangrove Restoration - Sinsin, Laurenda Corine Bitossessi; SALAKO, Valère; Tohoun, Roméo Jesukpégo; Glèlè kakaï, Romain (My University, 2022)
Mangroves are coastal wetland ecosystems of tropical and subtropical regions. Water and substrate salinities are important drivers of their development and trajectories. Therefore, understanding how main mangrove species respond to salinity gradient when transplanted in natural environment is essential for their restoration. This study assessed the survival, growth, and productivity of Rhizophora racemosa seedlings in response to gradient of salinity. Seedlings were grown in nursery under low (3–5 psu) and medium (15–17 psu) water salinities for thirty days and transplanted to three mangrove sites with various salinities (4.6, 11.41, and 18.27 psu). Seedling survival and growth were monitored monthly for 6 months. At the end of month 6, total biomass was harvested and partitioned among plant parts. Results showed that growth, survival, and productivity of R. racemosa were mainly infuenced not by the salinity under which the seedlings were raised in nursery but rather by site. Survival was higher (88.33%) at the site with the highest salinity. Total plant biomass was similar across sites, but root biomass and root weight ratio were higher on sites with higher salinity. Biomass was disproportionately higher in stems (45–54%) than in roots (28–37%), and leaves (15–18%). We suggest that restoration is done in appropriate period, ideally one month before the start of rainy season. This will not only allow seedlings to well establish their rooting system before rains start but also favour seedling growth, because of substrate salinity dilution by fresh water from rains and fows from uplands.
Keywords: Red mangrove · Restoration · Salinity · Nursery · Growth · Biomass